After the fire [large type] - Mankell, Henning, 1948-2015 (Thorndike Press, 2017)
"Fredrik Welin is a seventy-year-old former surgeon who retired in disgrace years ago. He has retreated to a Swedish archipelago, where he lives alone on an island. He swims in the sea every day, cutting a hole in the ice if necessary. He is perfectly content to live out his days in quiet solitude. Until he wakes up one autumn evening to find his house on fire. Fredrik escapes just in time, wearing two left-footed boots. All that remains in the morning is a stinking ruin and evidence of arson. Fredrik cannot imagine why someone would do such a thing. The police are also stumped, and without another suspect, they begin to think Fredrik started the fire himself. Fredrik's peaceful, simple life has slipped away from him. Then, Lisa Modin, a local journalist who wants to write a story about the fire, comes into his life, and she awakens in him something that he thought was long dead. After the Fire is an intimate portrait of a recluse who is forced to open himself up to a world he'd left behind"--